Critique: measuring hydrogen stable isotope abundance of proteins to infer origins of wildlife, food and people. (April 2013) - Meier-Augenstein, Wolfram; Hobson, Keith A; Wassenaar, Leonard I
Measurement of the relative abundance of 2 H (expressed in δ 2 H values) in tissues of plants, wildlife and people has evolved into a powerful forensic tool. The approach is based on the strong linkage between spatial patterns of δ 2 H values in precipitation at local and continental scales, and the tissues of plants and animals produced on these 'isoscapes'. Unfortunately, despite this exciting potential, difficulties inherent in the measurement of δ 2 H values in complex organic materials such as proteins, as well as the accuracy of such measurements, and a reluctance to adopt strict quality assurance/QC approaches to address challenges associated with these measurements, has clearly limited this potential. These challenges are entirely avoidable and techniques now exist for the routine reliable measurement of δ 2 H values in materials of forensic interest that will allow completely comparable data among laboratories.